Determination of D-dimer Levels in Patients Who Survived and Died From COVID-19: A Case-control Study - Forough Faroughi; Mahnaz Modanloo; Mohammad Sadeghi; Behnaz Khodabakhshi; Iman Taghizadeh Firozjaie (Gonabad University of Medical Sciences, 2024)
Background: The COVID-19 has spread worldwide since December 2019 and continues to affect populations today. Studies have shown that changes in blood coagulation, as well as an increases in D-dimer levels, occur in patients with the COVID-19, leading to increased hospitalization and patient mortality. This study was conducted to determine the levels of D-dimer in patients who survived and those who died from COVID-19.  Methods: In this case-control study, the participants were divided into two case and control groups according to the outcome of the disease. This research was conducted at 5th Azar and Sayad Shirazi Hospital in Gorgan from March 20, 2020, to June 20, 2021. A total of 158 patients who were eligible for the study were retrospectively screened. Among these hospitalized patients, 107 were in the survivor group and 51 were in the deceased group. Clinical and laboratory parameters, as well as the results of confirmed cases of COVID-19, were analyzed retrospectively. Data were analyzed using descriptive statistics and SPSS software, version 21.  Results: The mean D-dimer levels of the patients in the survival and death groups were 1.48±2.09 and 2.62±2.55, respectively. This difference was confirmed to be statistically significant (P=0.007). The odds ratio interpretation showed that the chance of death due to COVID-19 in patients with high D-dimer levels is 1.29 times that of patients with lower D-dimer levels.  Conclusion: The D-dimer levels on admission can serve as one of the biomarkers to predict mortality in patients with COVID-19.